Analisis Gaya Kepemimpinan dalam Mempertahankan Keberlangsungan Usaha Pada Masa Pandemi Covid-19 Di Daerah Perbatasan: Gaya Kepemimpinan Transformasional dan Transaksional - Yeremia Niaga Atlantika; Veneranda Rini Hapsari; Benedhikta Kikky Vuspitasari (UNIVED Press, 2023)
The purpose of this study is to explain how the form of application of the leadership style of economic actors in maintaining business continuity in Bengkayang Regency. In addition, to find out whether the applied leadership style is considered effective. This study uses a descriptive type of research with a qualitative approach. The source of data in this study came from primary data obtained through in-depth interviews with predetermined informants. The data obtained was then processed using qualitative data analysis software NVivo 12. The results of this study describe leadership styles in maintaining business during the Covid-19 pandemic in border areas including transformational leadership styles and transactional leadership styles. The application of a leadership style that dominates business actors in border areas is a transformational leadership style, because leaders will tend to involve employees in strategic decisions according to the situation and conditions that occur. Thus the transformational leadership style can run effectively in various conditions that are happening in the business or business environment in border areas.